Pengembangan Bahan Ajar Berbasis RADEC untuk Meningkatkan Keterampilan Literasi Sains - Baehaki, Farhan; Murtafi’ah, Ni’matul; Kodariah, Liah (Universitas Insan Budi Utomo, 2023)
21st-century skills have become standard in graduate profiles designed by the government, including for prospective Medical Laboratory Technologists (ATLM). One of the skills that the government focuses on is developing literacy skills. Therefore, this research aims to develop RADEC-based teaching materials that can facilitate the development of literacy skills for prospective ATLM students. The research method used is Development & Validation whose steps consist of 1) literature review; 2) construction; and 3) Improvement. The development was carried out by involving 20 students from the Medical Laboratory Technology Study Program. The instruments used in the data collection process were expert validation sheets and readability test sheets. The research results show that teaching materials have very good validity (>80% suitability) in facilitating the development of scientific literacy skills. Therefore, the teaching materials developed can be implemented in lectures.